The Impact of Urbanization on Land Use Dynamics in Peshawar City District, Pakistan: A Geoinformatic Approach: Impact of Urbanization on Land Use Dynamics - Samiullah; Khan, Mohammad Aslam; Rahman, Atta ur; Gul, Shehla (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2021)
Peshawar City, the sixth largest city of Pakistan is also the capital and largest metropolis of Khyber Pakhtunkhwa province. It has seen extremely fast growth during the last twenty-five years whereby it’s built up area more than doubled between 1991 and 2012. These unprecedented changes in the built up area and population of the city district not only resulted in an unprecedented urban sprawl with a mixture of an increasingly dispersed pattern of residential and other urban land uses but also witnessed land use dynamics with far reaching implications. This paper analyses the spatial and temporal aspects of land use dynamics in Peshawar city district during 1991-2012 period. The paper discusses the present land use and the land use change between 1991 and 2012 along with the factors that are responsible for the land use change and their policy implications. Main objective of the study was to find out impact of urbanization on land use dynamics of the city. Both primary and secondary data were used for the study beside satellite images. The secondary data were generated from revenue record, real estate agents and developers. For calculation of land use dynamics in 1991 Landsat images were used while for the year 2012 SPOT 2.5m images were acquired from SUPARCO. ArcMap was main software used for analysis and presentation of results in spatial format. Results of the study reveal that there has been a tremendous growth of built up area around the core of the city that has drastically changed the land use dynamics of the city. Due to lack of any workable plan most of these expansions are in the form of unplanned sprawl in the form of ribbon development along the roads as well as leap frog growth mostly on prime farmland.